Laser Scanner Calibration Dependency On the Line Detection Method - Molder, Ago; Martens, Olev; Saar, Tonis; Land, Raul (Elektronika ir Elektrotechnika, 2015)
Calibration is an important step of 3D structured light laser scanners to be able to obtain an accurate measuring result. During the calibration a relation between the pixels in 3D laser scanner camera image and the real world units is made. Laser line detection method as part of the calibration process plays an important role in this calibration process, but this aspect has not been investigated before. In this paper the calibration and measurement result dependency from the laser line detection with pixel or sub-pixel resolution in the calibration process has been investigated. The calibration process of the developed 3D laser scanner has been described. The results show dependency between the laser line detection method in the calibration process and the final measurement results. DOI: http://dx.doi.org/10.5755/j01.eee.21.6.13765